Mitochondrial Toxicity of Azithromycin Results in Aerobic Glycolysis and DNA Damage of Human Mammary Epithelia and Fibroblasts - Xianpeng Jiang; Catherine Baucom; Robert L. Elliott (MDPI AG, 2019)
Mitochondria evolved from free-living bacteria via endocytosis within eukaryotic host cells millions of year ago. We hypothesized that antibiotics cause mammalian mitochondrial damage while causing bacterial lethality. Mitochondrial toxicity of azithromycin in human mammary epithelia MCF-12A and fibroblasts were tested by fluorescent and transmission electron microscopy. Gene expression and DNA damage were tested by real-time polymerase chain reaction (qPCR) and ELISA. We found azithromycin suppressed the mitochondrial membrane potential gradient of MCF-12A cells and fibroblasts. Ultrastructure exams showed that the antibiotic caused vacuolated and swollen mitochondria with disrupted cristae in MCF-12A cells and fibroblasts compared to the morphology of mitochondria in the cells without antibiotic treatment. Fluorescent microscopy also showed azithromycin-induced mitochondrial reactive oxygen species (ROS), superoxide, after 3 h of culture. The DNA oxidative damage product, 8-hydroxy-2’-deoxyguanosine (8-OHdG, significantly increased in the media after MCF-12A cells and fibroblasts were cultured in the media containing azithromycin for 24 h. Azithromycin upregulated gene expression of hypoxia inducible factor 1 alpha (HIF1a), glycolytic enzymes including hexokinase 2 (HK2), phosphofructokinase 1 (PFKM), pyruvate kinase muscle isozyme M2 (PKM2), and glucose transporters in MCF-12A cells and fibroblasts. Lactate production also increased in the culture media. After treatment with azithromycin, healthy MCF-12A and fibroblast cells increased aerobic glycolysis—the “Warburg Effect”—to generate energy. In summary, azithromycin caused mitochondrial toxicity, ROS overproduction, DNA oxidative damage, upregulation of the HIF1a gene, and aerobic glycolysis in healthy mammalian cells. Over-usage of antibiotics could contribute to tumorigenesis and neurodegeneration and aggravate existing mitochondria-associated diseases.